PERBANDINGAN METODE ADAPTIVE MINIMUM ERROR LEAST SIGNIFICANT BIT REPLACEMENT (AMELSBR) DAN DISCRETE COSINE TRANSFORM (DCT) UNTUK STEGANOGRAFI CITRA DIGITAL - Fajar Sidik; wamiliana wamiliana; Febi Eka Febriansyah (Jurnal Komputasi, 2018)
Insertion of secret messages with steganography is one way to hide secret messages. In this research we will compare AMELSBR and DCT methods based on web application using image as the media for hiding the secret message. The file format used are (.png) as input cover and stegoimage, andÂ  (.txt) as data inserted. The result shows that AMELSBR method better than DCT method for manipulation of brightness, contrast, and cropping.